Kinetics and Mechanism of Hydrolysis of Mono-2-chloro Aniline Phosphate in Buffer Medium - Choure, Nitin; Bhoite, S.A. (Asian Journal of Chemistry, 2010)
The kinetics of the hydrolysis of 2-chloro aniline phosphate monoester has been carried out in buffer solution at 50 ºC in the pH range 0.00 to 7.46. The rate of reaction increases with increase in pH up to 4.17. The maximum value at pH 4.17 is due to hydrolysis via mononegative and neutral species. Neutral and mononegative species have been found to be reactive at pH 0.00 to 2.00 and 2.00-7.46, respectively; their dinegative species have been found to be inert. The estimated rate has been confirmed by those determined from specific rate and fractions of the neutral species agree closely with the experimental rates. Bond fission, molecularity have been supported by Arrhenius parameters, solvent effect. The results suggest that the hydrolysis of monoester occurs by the cleavage of P-N bond.